North west london perinatal network (NWLPN) experiences of developmental care benchmarking. (7th June 2011) - Naylor, H; Ronnie, L; Hurlston, R; King, B; Warren, I
Abstract : North West London Perinatal Network (NWLPN) set up a Multi Disciplinary Developmental Care Benchmarking Group to design a benchmarking tool in two parts: The Sensory Environment with eight factors. Family Centred Care with four factors. Aims of the exercise were to describe, assess and evaluate the sensory environment and family centred care provided for babies and families in NWLPN neonatal units, identifying key strengths, areas for improvement and training needs. Using the benchmarking tool, each NWLPN completed a self assessment. Unit leads hosted a visit for 2 external leads from other units to validate the self assessment process by reviewing the evidence provided. Visits were facilitated by the NWLPN Lead Nurse or Deputy Lead Nurse. 73 multidisciplinary members of staff and 25 parents participated in seven benchmarking visits. A rating system, incorporating early, intermediate and advanced levels of achievement was used for assessment and reporting purposes for each factor. A three point action plan was agreed by each unit. Factor analysis highlighted local and Network strengths. Examples of innovative practice and recommendations for improvement facilitate implementation of high quality and equitable developmental and family centred care in NWLPN to meet the criteria defined in Principle 3: Care of the baby and family experience of DH Toolkit for High-Quality Neonatal Services. The process was evaluated using a nominal group technique to gain consensus about the strengths of the exercise, the challenges faced and how the experience could be improved. The project enhanced collaboration, multi disciplinary and partnership working for staff and families in NWLPN.